TINJAUAN HUKUM TERHADAP PELAKSANAAN PENGELOLAAN KEUANGAN DESA DI DESA BUNGIN KECAMATAN BOKAN KABUPATEN BANGGAI LAUT PROVINSI SULAWESI TENGAH: LEGAL REVIEW OF THE IMPLEMENTATION OF VILLAGE FINANCIAL MANAGEMENT IN BUNGIN VILLAGE, BOKAN SUB-DISTRICT, BANGGAI LAUT DISTRICT, CENTRAL SULAWESI PROVINCE - Robby Putra, Blasius Haryanto; Hasan, Almusawir; Nur, Mustawa (Faculty Of Law Bosowa University, 2020)
This study aims to determine village financial management in Bungin Village in accordance with the Minister of Home Affairs Regulation Number 113 of 2014 concerning Village Financial Management and the obstacles that occur in the implementation of village financial management in Bungin Village. This study used normative and empirical research methods and the data used were primary data and secondary data by interviewing 4 village officials and 5 communities in Bungin Village. The results of this study found that the implementation of village financial management in Bungin Village starting from the planning, implementation, administration and reporting stages was in accordance with Permendagri No. 113 of 2014 concerning Village Financial Management. However, at the accountability stage, Bungin Village did not publish accountability reports to the community. This shows that the financial accountability of villages in Bungin Village is not in accordance with Article 40 Paragraph (1) Permendagri Number 113 of 2014 concerning Village Financial Management. The obstacles in the implementation of village financial management in Bungin Village are inadequate human resources, lack of input from the community, inadequate facilities and infrastructure and late information from the district government regarding village financial disbursements.